ANTIMICROBIAL ACTIVITY AND THE QUANTITATIVE ANALYSES OF PHENOLIC COMPOUNDS AND HEAVY METALS OF RED MULBERRY EXTRACTS (MORUS RUBRA L.) FROM SERBIA - DIMITRIJEVIĆ, Danica; KOSTIĆ, Danijela; PAUNOVIĆ, Dušan; MITIĆ, Milan; KRSTIĆ, Jovana; RAŠIĆ MIŠIĆ, Ivana; ARSIĆ, Biljana (Studia Universitatis Babeș-Bolyai Chemia, 2022)
All investigated extracts of red mulberry (Morus rubra L.) contain a high content of total phenols. The highest content of total phenols was shown by red mulberry in the ethanolic extract (50%). Certain extracts of the fruit of red mulberry (aqueous, ethanolic 50%, acetonic 50% and acetonic) contain very small quantities of anthocyanins. Four phenolic acids were identified in the extracts of red mulberry: chlorogenic, neochlorogenic, cryptochlorogenic acid and caffeic acid, and four flavonoids using HPLC analysis: quercetin-3-O-rutinoside, quercetin-3-O-glucoside, quercetin-3-O-rhamnoside, and kaempferol-3-O-rutinoside. Cyanidin-3-O-glucoside was identified in the methanolic extract of red mulberry. The content of heavy metals (Fe, Cu, Mn, Cd, Ni, Zn and Pb) was determined using atomic absorption spectroscopy in fruits and the extracts of red mulberry. Mulberry fruit has been shown the highest content of Fe and low content of toxic metals. The content of metals is the highest in the majority of cases in the extracts of acetone and acetone 50%. The methanolic extract of red mulberry shows the antimicrobial properties against all investigated bacteria except Staphylococcus aureus. Obtained results show that fresh fruits of red mulberry and its extracts can be used in nutrition and the preparation of pharmaceutical formulations.